ALLOCATION SOLUTIONS FOR RECYCLED MUNICIPALWASTE AGGREGATES - Hadi Abou Chakra; Meheddene Machaka (European Scientific Journal, ESJ, 2015)
Municipal waste presents major environmental and public health concerns. The disposal of municipalwaste has become a major worldwide environmental problem. Landfill sites are considered as environmentally questionable option and their capacity are decreasing rapidly. Nowadays, various processes have emerged to recycle the waste as synthetic fuel gas, heat source, polymers, fertilizers, and particulate solid residues. In this study, the possibility of recycling these particulate solids as aggregate in concrete was considered. The physical properties and size distribution of recycled aggregates were measured along with the effect of using these recycled aggregate on the compressivestrength of concrete. The resulting outcomes of these tests were compared with concrete sample prepared with conventional crushed stone as coarse aggregate and natural sand as fine aggregate materials. No doubt, recycled aggregates can be used as a replacement of natural course and fine aggregates, but there is need for further investigations about its effect on the concrete properties.